The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4067/s0717-95022015000400052
|View full text |Cite
|
Sign up to set email alerts
|

Both Hepatic Lipogenesis and Beta-Oxidation are Altered in Offspring of Mothers Fed a High-Fat Diet in the First Two Generations (F1 and F2)

Abstract: SUMMARY:The high fat (HF) fed mothers may program susceptibility in offspring to chronic diseases and affect subsequent generations. The present study evaluated the liver structure in adulthood, focusing on the F1 and F2 generations. Females C57BL/6 (F0) were fed standard chow (SC) or HF diet (8 weeks) prior to mating and during the gestation and lactation to provide the F1 generation (SC-F1 and HF-F1). All other mothers and offspring fed SC. At 3 months old, F1 females were mated to produce the F2 generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We found no significant effects on grand-offspring traits of treatment animals from one-off experiments, although the effect was in the expected direction. Others have shown that subtle effects of obesogenic diets can persist beyond the F0 generation even without further diet manipulation, [71][72][73][74] whereas our meta-analysis highlights that there is uncertainty and heterogeneity regarding this effect. In contrast, grand-offspring traits of treatment animals from multigenerational experiments were 43% higher than their control counterparts.…”
Section: One-off Vs Multigenerational Exposurementioning
confidence: 68%
See 1 more Smart Citation
“…We found no significant effects on grand-offspring traits of treatment animals from one-off experiments, although the effect was in the expected direction. Others have shown that subtle effects of obesogenic diets can persist beyond the F0 generation even without further diet manipulation, [71][72][73][74] whereas our meta-analysis highlights that there is uncertainty and heterogeneity regarding this effect. In contrast, grand-offspring traits of treatment animals from multigenerational experiments were 43% higher than their control counterparts.…”
Section: One-off Vs Multigenerational Exposurementioning
confidence: 68%
“…Grand-offspring traits of treatment animals from One-off experiments tended to be 9% higher than control grand-offspring, although this overall effect was statistically non-significant. This finding is unsurprising, as it has been previously shown that subtle effects of obesogenic diets can persist beyond the F0 generation even without further diet manipulation [71][72][73][74] .…”
Section: One-off Vs Multigenerational Exposurementioning
confidence: 97%